The effect on shikimate production by deleting iolR and metabolic engineering in PTS deficient Corynebacterium glutamicum strain - Ou, Rui Wen; Swofford, Charles A.; Zhong-Johnson, En-Ze Linda; Li, Cheng; Sinskey, Anthony J. (Frontiers in Bioengineering and Biotechnology, 2025)
Shikimate is a precursor to many high-value chemical derivatives. Several bacteria have been engineered to produce high titer of shikimate via non-phosphotransferase system (Non-PTS), but yet explores how the myo-inositol utilization transcription regulator (iolR) deletion affects the shikimate titer in phosphotransferase system (PTS) deficient strain. In this study, we engineered Corynebacterium glutamicum to produce shikimate in a PTS deficient strain with the deletion of iolR and improved shikimate production using a metabolic engineering approach. PTS was eliminated to improve phosphoenolpyruvate levels, however, both the cell growth rate and shikimate production were dramatically reduced. Hence, iolR was deleted to improve cell growth and shikimate production in the PTS deficient strain. In addition, we overexpressed genes in the glycolysis and shikimate pathways to increase shikimate production. The combination of the strategies resulted in a shikimate content of 0.76 mg/mg of DCW and a titer of 4.1 g/L in shake flask in C. glutamicum, providing novel insights for further engineering to enhance production of shikimate and its derivatives.